Compression of coated drug beads for sustained release tablet of glipizide: formulation, and dissolution. (1st February 2014) - Nguyen, Chien; Christensen, J. Mark; Ayres, James W.
Abstract: A promising glipizide formulation comprising compression of four-layer coated beads into tablets was prepared. The tablet offered the advantages of: a two-hour lag time before drug release, retaining sustained release characteristics and providing approximately zero-order drug release. Drug release was nearly independent of paddle speeds of 50 and 100 rpm releasing 80% over 14 h similar to the commercial glipizide osmotic pump tablet during dissolution testing while keeping the benefits of multiparticular dosage forms. The tablets contain beads with four layers: (1) the innermost layer consists of 2.5 g glipizide and 3.75 g solid ethylcellulose (Surelease®) coated onto 71.25 g of sugar beads; (2) next a hardening layer of 5 g of hypromellose; (3) the controlled release layer of 7.5 g of Surelease®:lactose at a solids ratio of 100:7 and (4) an outermost layer of 20 g of lactose:sodium starch glycolate (Explotab®) at a 2:1 ratio. Then, beads were compressed into tablets containing 11 mg of glipizide using 1500 lbs of compression pressure. The dissolution test similarity factor ( f 2 ) was above 50 for all test conditions for formulation F13 and Glucotrol® with a high of 69.9. The two Surelease® layers both aid controlling drug release, with the Surelease®-drug layer affecting drug release to a greater extent.